Neuroprotective effects of hypothermia in inflammatory‐sensitized hypoxic‐ischemic encephalopathy. Issue 55 (9th September 2016) - Chevin, Mathilde; Guiraut, Clémence; Maurice‐Gelinas, Caroline; Deslauriers, Jessica; Grignon, Sylvain; Sébire, Guillaume
Abstract: Background: Despite the recent introduction of hypothermia as a mandatory standard of care, the incidence of neonatal encephalopathy in full‐term newborns and its devastating neuro‐behavioral outcomes continues to be a major individual, familial and social issue. Neonatal encephalopathy is mainly due to the compounding and interacting effects of hypoxia‐ischemia and inflammation resulting from placental and other perinatal infections. It is unclear why hypothermia is effective in alleviating neonatal encephalopathy in some, but not all, full‐term newborns. However, newborns exposed to inflammatory‐sensitized hypoxia‐ischemia seem to have less therapeutic benefit from hypothermia than those exposed to hypoxia‐ischemia alone. Objectives: To clarify this uncertainty, we tested the efficacy of hypothermia in a double‐hit model of neonatal encephalopathy induced by inflammatory‐sensitized hypoxia‐ischemia. Methods: Using a rat preclinical model of endotoxin plus hypoxia‐ischemia‐induced neonatal encephalopathy of term newborns, we assessed the following in pups exposed (or not) to hypothermia: the extent of brain injuries and the expressions of molecules implicated in neural cell death, namely: pro‐inflammatory cytokines, matrix metalloproteinase‐9, antioxidant enzymes, as well as receptor‐interacting protein‐3. Results: Hypothermia was neuroprotective on inflammatory‐sensitized hypoxia‐ischemia‐induced penumbra, but not core, brain injuries. This beneficial effect was associated with a hypothermia‐induced increase of antioxidant enzymes (superoxide dismutase‐1, glutathione peroxidase‐1), but was not associated with any variations of the other inflammatory mediators tested, namely: interleukin‐1β, interleukin‐1 receptor antagonist, tumor necrosis factor‐α and matrix metalloproteinase‐9. Conclusion: Hypothermia is neuroprotective against inflammatory‐sensitized hypoxia‐ischemia possibly through a hypothermia‐induced increase of antioxidant enzymes. This neuroprotective effect seems to be independent of the interleukin‐1 system.